1985
DOI: 10.1128/iai.48.3.847-849.1985
|View full text |Cite
|
Sign up to set email alerts
|

Chronic chlamydial genital infection in congenitally athymic nude mice

Abstract: Congenitally athymic nude mice and their heterozygous counterparts were inoculated intravaginally with the chlamydial agent of mouse pneumonitis, a Chlamydia trachomatis biovar. Heterozygous mice resolved their infections in 20 days, whereas nude mice developed chronic infections which lasted at least 265 days and did not resolve within the time course of the experiments. Heterozygous mice produced high levels of antibody in both serum and secretions in contrast to nude mice, which produced very low levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 10 publications
1
56
1
Order By: Relevance
“…Our observations support and extend other findings. A study of the infection in nude mice (19) also demonstrated that resolution is a T-cell-dependent mechanism. However, since nude mice did not develop significant antibody titers to MoPn, it was not known whether this was a result of absence of T-cell-dependent help for the antibody response or of absence of CMI mechanisms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our observations support and extend other findings. A study of the infection in nude mice (19) also demonstrated that resolution is a T-cell-dependent mechanism. However, since nude mice did not develop significant antibody titers to MoPn, it was not known whether this was a result of absence of T-cell-dependent help for the antibody response or of absence of CMI mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated that the primary infection results in immunity to reinfection and that both humoral and CMI responses are elicited (3). Furthermore, evidence gathered about unresolved chronic infections of congenitally athymic nude mice has indicated that T cells play a significant role in the resolution of the infection (19). However, since nude mice did not produce significant antibody titers, it could not be determined if the chronic infection resulted from the absence of T-ce' dependent antibody responses or from the absence of CMI mechanisms.…”
mentioning
confidence: 99%
“…These results are the first to definitively show in a side-by-side study that adaptive and innate immunity play distinct roles in control of C. muridarum and C. trachomatis infection of the female mouse genital tract. Tuffrey et al (1982) and Rank et al (1985) previously reported on C. trachomatis and C. muridarum infection of the female genital tract in nude mice, respectively. Their findings were similar to those described herein; C. trachomatis infection of the female mouse genital tract resolved spontaneously in the absence of T cells (Tuffrey et al, 1982), whereas T cells were required for the resolution of C. muridarum infection (Rank et al, 1985).…”
Section: Introductionmentioning
confidence: 97%
“…Tuffrey et al (1982) and Rank et al (1985) previously reported on C. trachomatis and C. muridarum infection of the female genital tract in nude mice, respectively. Their findings were similar to those described herein; C. trachomatis infection of the female mouse genital tract resolved spontaneously in the absence of T cells (Tuffrey et al, 1982), whereas T cells were required for the resolution of C. muridarum infection (Rank et al, 1985). An important difference between those studies and ours is that these investigators used nude mice which have a greatly reduced, but not complete deficiency, in T cell immunity (Belizario, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…However, in the murine system, several lines of evidence suggest that T-cell-mediated immunity is the principal immune mechanism for controlling chlamydial genital disease. Thus, B-celldeficient mice could resolve chlamydial genital infection as efficiently as immunocompetent age-matched mice (14), whereas athymic (nude) mice were persistently infected after a primary genital infection (19). Moreover, murine T-cell lines (13) and CD4+ clones (3) could resolve the persistent chlamydial genital infection in nude mice.…”
mentioning
confidence: 99%